2015
DOI: 10.1002/anie.201503532
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 1,2,4‐Oxadiazole and 1,2,5‐Oxadiazole Moieties for the Generation of High‐Performance Energetic Materials

Abstract: Salts generated from linked 1,2,4-oxadiazole/1,2,5-oxadiazole precursors exhibit good to excellent thermal stability, density, and, in some cases, energetic performance. The design of these compounds was based on the assumption that by the combination of varying oxadiazole rings, it would be possible to profit from the positive aspects of each of the components. All of the new compounds were fully characterized by elemental analysis, IR spectroscopy, (1)H, (13)C, and (in some cases) (15)N NMR spectroscopy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 169 publications
(104 citation statements)
references
References 38 publications
3
98
0
Order By: Relevance
“…The combination of 1,2,4-oxadiazole and 1,2,5-oxadiazole moieties allowed the synthesis of salts, such as 166, that exhibit good thermal stability, relatively high density, and, in some cases, energetic performance (15AGE9367).…”
Section: Oxadiazolesmentioning
confidence: 99%
“…The combination of 1,2,4-oxadiazole and 1,2,5-oxadiazole moieties allowed the synthesis of salts, such as 166, that exhibit good thermal stability, relatively high density, and, in some cases, energetic performance (15AGE9367).…”
Section: Oxadiazolesmentioning
confidence: 99%
“…[2] To design new highperformance energetic materials,i ntroducing energy-rich functional groups such as -NO 2 ,-NHNO 2 ,-N =N-, and -N= N(O)-as substituents on azole frameworks is ar ecently emerging methodology. [4] Among the combinations between functional moiety and azole backbone,the family of nitramino-furazans has gained particular attention because of its high detonation properties. [4] Among the combinations between functional moiety and azole backbone,the family of nitramino-furazans has gained particular attention because of its high detonation properties.…”
mentioning
confidence: 99%
“…[5] It can be easily attributed to the presence of al arger number of nitrogen atoms and -C=Nbonds in the two ring systems.Ina ddition, by comparing the heats of formation of the directly coupled furazans (4,4'dinitramino-3,3'-bifurazan), 4,4'-bis(nitramino)azofurazans (DNAF), and 4,4'-bis(nitramino)azoxyfurazans (DNAXF), it is found that azo and azoxy linkages also play an important role in increasing the heat of formation. [6] Given this background, we herein report that 1, as well as ten of its nitrogenrich ionic derivatives (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), were efficiently synthesized and fully characterized (Scheme 1). [6] Given this background, we herein report that 1, as well as ten of its nitrogenrich ionic derivatives (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), were efficiently synthesized and fully characterized (Scheme 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations